Phosphorus status of amended soil as assessed by conventional and isotopic methods - Bah, Abdul R.; Zaharah, A.R.; Hussin, A.; Husni, M.H.A.; Halimi, M.S. (Informa UK Limited, 2003)
Organic manures and phosphate rocks (PRs) can greatly enhance phosphorus (P) availability in soils with high P fixation. However, the pathways by which this occurs are still not well understood. Reliable estimation of P pools and available P dynamics can greatly assist in the identification of these mechanisms. The effect of PRs and green manures (GMs) on soil P status was evaluated by conventional and isotopic methods in an amended acid soil (Selangor series) after 64 weeks of incubation. The treatments were factorial combination of P fertilizers-PRs from Algeria, China and North Carolina (APR, CPR and NCPR) plus triple super phosphate (TSP)-and GMs from legumes Calopogonium (Calopogonium caeruleum) and Gliricidia (Gliricidia sepium), and a non-legume-Imperata (Imperata cylindrica). Soil samples were analyzed for available P, P fractions, sorption characteristics, and pools of P that are exchangeable at various times using 32P isotope exchange kinetics. The legume GMs reduced P sorption maximum by over 80%, and the GMs alone or together with P fertilizers made significant improvements in available P, and increased P in Fe-P (> 2 times) and A1-P (18 - > 20 times) fractions, which made up the pools that are exchangeable in less than 1 year. Phosphate from the legume GMs saturated sorption sites by reversible sorption, while that from P fertilizers was irreversibly retained and expanded the unavailable fraction to over 90% of total P. The importance of GMs in the management of P in high P-retaining soils is reaffirmed.